Baby Car Seat With Warning System Using IoT - Nurul Fatin Izzati Abdul Rasid; Zohari, Mohd Hakimi (Progress in Engineering Application and Technology, 2022)
In this advancement era, the bustling of daily schedule makes individuals particularly parents contribute to a lot of tragic cases that involve the death of children inside the left vehicle. This incident can happen because of parental carelessness therefore the ideas of this project are able to help by detecting and warning parents regarding to the presence of a baby in car seat. The system designed will be having two separate boards consist of weight sensor with amplifier and two microcontrollers. By using this new transformation, it will send push notification to driver via mobile apps and guardian email. Thus, this project will become one of the new innovations of baby car seat according to our modern technology which are efficient, user friendly and conveniently used.